ONLINE TEACHING PREPAREDNESS AND STRESS PROFILE: A COMPARATIVE STUDY OF SECONDARY AND HIGHER EDUCATION FACULTY EXPERIENCES IN THE PHILIPPINES - Jordan Pocaan; Lyndon Bailon; Jean Pauline Pocaan (Tạp chí Khoa học Đại học Đà Lạt, 2022)
The shift of education to online learning requires every educator to adjust; but the adjustment causes teachers to feel stress and requires preparation. This study purposively explores and compares the online teaching preparedness and stress profile of 100 secondary and 200 higher education faculty. The study uses a sequential explanatory research design consisting of a survey followed by interviews. The results reveal that higher education faculty are better prepared to teach online than secondary education faculty. The lack of emergency response to power service interruption and low internet connectivity are the major problems faced by the participants. Secondary and higher education faculty have the same level of stress from online teaching. It was concluded that educators at both private public and private institutions can aid teachers in combating the challenges of teaching online, online teaching devices, relevant educational technology tools, and faculty training and workshop on stress management. Investigating teacher development positively affects the learning achievement of the students.